Magnetic resonance imaging evaluation of incidentally detected hyperechoic liver lesions: comparison of two modalities in terms of detection, diagnosis, and morphological features - Soker,Gokhan (2021)
SUMMARY OBJECTIVE: This study aimed to investigate and compare the ultrasonography and contrast-enhanced magnetic resonance imaging characteristics of incidentally detected hyperechoic focal liver lesions. METHODS: Seventy-four patients (29 males and 45 females) who had undergone a B-mode ultrasonography and contrast-enhanced magnetic resonance imaging examination were included in this study. A total of 91 hyperechoic lesions detected on ultrasonography were evaluated. The ultrasonography features of these hyperechoic lesions were recorded, and the results were compared with those acquired from contrast-enhanced magnetic resonance imaging. The results were compared statistically using the Shapiro-Wilk, McNemar, and Wilcoxon signed-rank tests. RESULTS: A corresponding lesion was found on contrast-enhanced magnetic resonance imaging in 72 of the 91 (79.1%) hyperechoic lesions detected on ultrasonography. Forty-one (56.9%) of the magnetic resonance imaging-defined lesions were typical hemangiomas, while 10 (13.9%) were focal steatosis areas and 4 (5.6%) were diagnosed with hepatocellular carcinoma. In contrast, 6 lesions (8.3%) were diagnosed as simple hepatic cysts, 4 (5.6%) as sclerosing hemangioma, 2 (2.8%) as thrombosed hemangioma, 1 (1.4%) as focal nodular hyperplasia, 1 (1.4%) as hamartoma, 2 (2.8%) as hydatid cysts, and 1 (1.4%) as hepatic lipoma. No statistically significant differences were found between ultrasonography and magnetic resonance imaging in terms of the segmental classification of the true positive lesions based on contour structures and lesion area measurements (p=0.558, p=0.375, and p=0.636, respectively). CONCLUSIONS: Incidentally detected hyperechoic zones may not necessarily be detected on magnetic resonance imaging. This may be secondary to focal hepatic steatosis or false interpretation of the radiologist. Lesions requiring therapy must be considered in the differential diagnosis.